Automotive Breathanalyzer to Detect Alcohol Consumed Driver - Sushma, I.Sri Phani; Mudavath, Balaji Naik; Lakshmi, G.N.Dhana; G. Anil, G. Anil; Lakshmi, D.K.; Kumar, K.Ganesh; Pavan, G.D. (Journal of Neonatal Surgery, 2025)
This project presents a smart Breath Analyzer System developed using an Arduino Uno, which detects the presence of alcohol in a person's breath and takes appropriate actions. The core component of the system is an alcohol sensor (MQ-3), which accurately senses alcohol content when the user breathes near it. Upon detecting alcohol above a predefined threshold, the system triggers a buzzer alarm, displays a warning message on an LCD screen, and sends real-time data through Wi-Fi (ESP8266 module) to a cloud server or mobile app for remote monitoring. Additionally, DC motors simulate vehicle ignition control, where the system prevents engine startup when alcohol is detected—ensuring enhanced safety. This feature can be integrated into vehicles to restrict drunk driving [5][6]. The combination of hardware and communication modules makes the system efficient, affordable, and suitable for both personal and commercial use. The breath analyzer aims to reduce road accidents caused by drunk driving and promote responsible behavior through a reliable and user-friendly embedded solution